Public finance of universal routine childhood immunization in India: district-level cost estimates. Issue 2 (15th September 2021) - Schueller, Emily; Nandi, Arindam; Summan, Amit; Chatterjee, Susmita; Ray, Arindam; Haldar, Pradeep; Laxminarayan, Ramanan
Abstract: India's Universal Immunization Programme (UIP) is among the largest routine childhood vaccination programmes in the world. However, only an estimated 65% of Indian children under the age 2 years were fully vaccinated in 2019. We estimated the cost of raising childhood vaccination coverage to a minimum of 90% in each district in India. We obtained vaccine price data from India's comprehensive multi-year strategic plan for immunization. Cost of vaccine delivery by district was derived from a 2018 field study in 24 districts. We used propensity score matching methods to match the remaining Indian districts with these 24, based on indicators from the National Family Health Survey (2015–16). We assumed the same unit cost of vaccine delivery in matched pair districts and estimated the total and incremental cost of providing routine vaccines to 90% of the current cohort of children in each district. The estimated national cost of providing basic vaccinations—one dose each of Bacillus Calmette–Guerin (BCG) and measles vaccines, and three doses each of oral polio (OPV) and diphtheria, pertussis and tetanus vaccines—was 784.91 million (2020 US). Considering all childhood vaccines included in UIP during 2018–22 (one dose each of BCG, hepatitis B and measles–rubella; four doses of OPV; two doses of inactivated polio; and three doses each of rotavirus, pneumococcal and pentavalent vaccines), the estimated national cost of vaccines and delivery to 90% of target children in each district was 1.73 billion. The 2018 UIP budget for vaccinating children, pregnant women and adults was 1.17 billion (2020 US). In comparison, 1.73 billion would be needed to vaccinate 90% of children in all Indian districts with the recommended schedule of routine childhood vaccines. Additional costs for infrastructural investments and communication activities, not incorporated in this study, may also be necessary.